2020
DOI: 10.1002/jsc.2339
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance and financial inclusion: Challenges and opportunities

Abstract: Lifting the poor from poverty through financial and social inclusion is the ultimate target and raison d'etre of microfinance. As the most recent literature has recognized, microfinance institutions have economically worked well in operating microcredit, but the aim of raising the living standard of their indigent clients has not been generally met. The expected encouragement of entrepreneurship from microcredit is still not detected in the empirical data, let alone women's social integration in working activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 105 publications
0
39
0
3
Order By: Relevance
“…Many academics, governments, investors, and development actors held very high hopes about microfinance as the industry emerged. Since then, however, it has been much more criticized (Milana & Ashta, 2020). While some scholars have argued that its promises are not always met (Weiss & Montgomery, 2005), ethical issues have also tarnished the industry's reputation (Hudon & Sandberg, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many academics, governments, investors, and development actors held very high hopes about microfinance as the industry emerged. Since then, however, it has been much more criticized (Milana & Ashta, 2020). While some scholars have argued that its promises are not always met (Weiss & Montgomery, 2005), ethical issues have also tarnished the industry's reputation (Hudon & Sandberg, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this arena, there are indications of new technologies, such as mutual support systems, interdependent credit systems, village savings, credit banks, and credit systems for microenterprises (Jawadi, Jawadi, & Dechamps, 2010;Khavul, 2010). In all of these, the role of technological innovations in enabling new means of performing transactions, monitoring customers, and contributing to microfinance is highlighted (Milana & Ashta, 2020;Singh & Padhi, 2015).…”
Section: Microfinance and Technologymentioning
confidence: 99%
“…As in the banking sector, the microfinance sector is impacted by technological changes, and these changes directly contribute to the ability to reach out and achieve the win-win situation (Milana & Ashta, 2020;Singh & Padhi, 2015). Some of these technologies are related to the development of fintechs (Liu et al, 2020) -including e-banking, apps, and mobile payment -that are already being used by MFIs (Elliot et al, 2018;Jawadi et al, 2010).…”
Section: Microfinance and Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…The national household survey in 2003 revealed that only 27% of the households were indebted to formal sources (NSSO, 2006). Low‐income households claim that accessing credit from formal sources is too expensive (Milana & Ashta, 2020). Therefore, they continue to access credit from informal moneylenders for their consumption needs as, here, the process of accessing credit is more straightforward and does not involve nonprice barriers and transaction costs (Parekh & Ashta, 2018).…”
Section: Literature Review and Hypothesismentioning
confidence: 99%